Synthesis and Characterization of Nio Nanocrystals by using Sol-Gel Method with Various Precursors - Ningsih, Sherly Kasuma Warda; Khair, Miftahul (Makara Journal of Science, 2017)
Nickel oxide (NiO) nanocrystals were synthesized by simple sol-gel method at low temperature by using methanol as the solvent and NaOH 5M as the precipitation agent. Nickel nitrate hexahydrate, nickel acetate tetrahydrate and nickel sulfate hexahydrate were used as the precursors. The crystals were formed by drying at 100-110 °C for ± 1 hour, after which they were heated at ± 450 °C for 1 hour. The resulting products were black powders. The as-prepared NiOnanocrystals were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD patterns of the NiO nanocrystals showed that they are mostly cubic. The sizes of the NiO particles produced with nickelnitrate hexahydrate, nickel acetate tetrahydrate and nickel sulfate hexahydrate were 72.16, 38.63 and 32.84 nm, respectively. SEM images showed that the nanopowders produced by the precursors are spherical, rod-shaped andhexagonal shape with hollow, respectively.